Al-Badal wa I’rābuhu fī Kitāb Ta’līm al-Muta’allim Thorīqa al-Ta’allum li as-Syeikh Burhani al-Islam al-Zarnouji - Cholis, Agung Nur; Silfiawati, Masnunatus; Alfiroh, Nila (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2023)
This research aims to get the word that falls instead in Ta’lim al-Muta’allim Thoriqa at-Ta’allum of Sheikh Burhanul al-Islam al-Zarnouji. The methodology used (Documentary Method), which relate to the research to be researched by the researcher, which is the in ta’lim Muta’allim thoriqat ta’allum of Sheikh Burhan Islam Al-Zarnouji. The curriculum for the Arabic term is for the researcher to choose from the limits of the form and its definitions, her plains, and the whole of them for the term's meaning. Then the parts of the definitions discuss a discussion that discovers their dimensions in all respects. It then mentions grammar that explains the Arabic side, in particular, accompanied by its testimonies and representation, and its explanations only mention the language's logic. After studying allowance seekers in ta’lim Muta’allim thoriqat ta’allum of Sheikh Burhan Islam Al-Zarnouji, the researcher found 73 words that become instead.